Research status and trend of coupling between nitrogen cycle and arsenic migration and transformation in groundwater systems - Huaming GUO; Zhipeng GAO; Wei XIU (Shuiwen dizhi gongcheng dizhi, 2022)
The coexistence of ammonium, arsenic and dissolved iron in groundwater is a common phenomenon in aquifer systems. They have a strong interaction and affect the nitrogen cycling and the migration and transformation of arsenic in groundwater systems. Based on the systematic survey of international and national literature on the process and influencing factors of groundwater nitrogen cycling, the functional microorganisms and their characteristics related to groundwater nitrogen cycling, and the hydrogeochemical process of arsenic enrichment in groundwater, this paper deciphers effects of nitrogen cycling (including nitrification, denitrification, Feammox, Anammox, and dissimilatory nitrate reduction to ammonium) on the migration and transformation of arsenic in groundwater. We proposed that the dynamic transformation of iron oxides and dissolved Fe (II) in aquifers is an important bridge for nitrogen cycling and the migration and transformation of arsenic in groundwater. The processes of nitrogen cycling in aquifers with different redox environments, the coupling mechanism between nitrogen cycling and arsenic migration and transformation, the interactions among Fe(III) - Fe(II) cycling, nitrogen cycling, and arsenic migration and transformation, nitrogen-iron-arsenic cycling in the surface water-groundwater interaction zone and its response to human activities are important scientific issues and research trend that need to be paid attention to in this field in the future. The solution of these scientific problems is not only conducive to identifying the source, migration and transformation of nitrogen in groundwater, but also beneficial to improving the systematical understanding of enrichment mechanism of groundwater arsenic.